COMPREHENSIVE EVALUATION OF CERVICAL CANCER RISK QUESTIONNAIRES: ANALYZING DEMOGRAPHIC, BEHAVIORAL, ENVIRONMENTAL DIMENSIONS - Indah Mauludiyah; Miftakhul Mahfirah Ermadona; Achmad Zani Pitoyo (Menara Medika, 2024)
Background: Cervical cancer is highly preventable and treatable if detected early; however, many women still face serious consequences due to this cancer. Late screening is one of the primary risk factors contributing to the incidence of cervical cancer. Problem: Many studies that use questionnaires to assess cervical cancer risk factors often lack a thorough evaluation of the instruments' validity, reliability, and appropriateness, underscoring the need for comprehensive assessment. Objective: This study aims to evaluate questionnaires related to cervical cancer risk factors by assessing their validity, reliability, and suitability. Method: A systematic review was conducted based on the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines, analyzing studies published from 2014 to 2024. Nine papers were reviewed, focusing on questionnaire characteristics, including the number of items, item types, and validity assessment methods. Results: The analysis showed that 56% of the studies used questionnaires with fewer than 50 items, and all studies used closed-item formats. In 44% of the studies, the number of items was not disclosed. The highest percentage of studies (44%) involved using questionnaires adapted from previous research. Regarding validity, 44% of the studies employed Cronbach's alpha as a measure. Conclusion: Questionnaires used in studies on cervical cancer risk factors exhibit variation in characteristics and validity assessment methods. To improve questionnaire quality, it is crucial to ensure clear disclosure of item counts and robust validity and reliability assessments.